Spherical Mapping based Load Aware Routing for Wireless Sensor Networks - Fatima Muhammad Anwar (The Graduate School, Ajou University, 2011)
Energy management and Routing issues are correlated in most of the applications for Wireless Sensor Networks (WSNs). Routing in WSNs mainly focuses on Geographical/Shortest Path Routing (SPR) which takes linear shortest distance as the routing metric. The shortest traveled distances mostly traverse through the centre of the network that leads to the uneven distribution of traffic load. This results into more energy consumption in the central region of the network. As a solution, in this thesis, the energy usage fairness is introduced by proposing a type of routing which balances the load in the entire network. We propose Spherical Mapping based Routing (SMR) which maps a grid onto a sphere using spherical coordinates and takes circular shortest distance on the surface of the sphere as the routing metric. Our protocol not only balances the load but also makes sure that the average load and stretch factor for the network do not go out of bounds. In our analytical and simulation evaluation, we have compared our routing protocol with the state of the art work in the load balancing routing. We deduce an improvement of 26% in the stretch factor, and 33% in the average load per node ？ that results into fair energy distribution per node.
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2011. 2
Keywords: Spherical Mapping; Wireless Sensor; Load Aware Routing